Radiosynthesis and biological evaluation of 18F-labeled 4-anilinoquinazoline derivative (18F-FEA-Erlotinib) as a potential EGFR PET agent. Issue 6 (1st April 2018) - Huang, Shun; Han, Yanjiang; Chen, Min; Hu, Kongzhen; Qi, Yongshuai; Sun, Penghui; Wang, Men; Wu, Hubing; Li, Guiping; Wang, Quanshi; Du, Zhiyun; Zhang, Kun; et al.
Graphical abstract: Highlights: Synthesis of a novel 18 F-labelled 4-anilinoquinazoline derivative ( 18 F-FEA-Erlotinib). 18 F-FEA-Erlotinib is a promising PET tracer for screening EGFR TKIs sensitive patients. The potential of 18 F-FEA-Erlotinib was shown by PET imaging in tumor-bearing mice. Abstract: Epidermal growth factor receptor (EGFR) has gained significant attention as a therapeutic target. Several EGFR targeting drugs (Gefitinib and Erlotinib) have been approved by US Food and Drug Administration (FDA) and have received high approval in clinical treatment. Nevertheless, the curative effect of these medicines varied in many solid tumors because of the different levels of expression and mutations of EGFR. Therefore, several PET radiotracers have been developed for the selective treatment of responsive patients who undergo PET/CT imaging for tyrosine kinase inhibitor (TKI) therapy. In this study, a novel fluorine-18 labeled 4-anilinoquinazoline based PET tracer, 1 N -(3-(1-(2- 18 F-fluoroethyl)-1 H -1, 2, 3-triazol-4-yl)phenyl)-6, 7-bis(2-methoxyethoxy)quinazolin-4-amine ( 18 F-FEA-Erlotinib), was synthesized and biological evaluation was performed in vitro and in vivo. 18 F-FEA-Erlotinib was achieved within 50 min with over 88% radiochemical yield (decay corrected RCY), an average specific activity over 50 GBq/μmol, and over 99% radiochemical purity. In vitro stability study showed no decomposition of 18 F-FEA-Erlotinib after incubated in PBS and FBS for 2 h. Cellular uptake and efflux experiment results indicated the specific binding of 18 F-FEA-Erlotinib to HCC827 cell line with EGFR exon 19 deletions. In vivo, Biodistribution studies revealed that 18 F-FEA-Erlotinib exhibited rapid blood clearance both through hepatobiliary and renal excretion. The tumor uptake of 18 F-FEA-Erlotinib in HepG2, HCC827, and A431 tumor xenografts, with different EGFR expression and mutations, was visualized in PET images. Our results demonstrate the feasibility of using 18 F-FEA-Erlotinib as a PET tracer for screening EGFR TKIs sensitive patients.